GAMBARAN KONFLIK INTRAPERSONAL & PERCEIVED SOCIAL SUPPORT PADA IBU YANG KEMBALI BEKERJA SETELAH MEMILIKI ANAK PERTAMA - Carrisa Christianty Putri; Fransisca Rosa Mira Lentari (MANASA, 2020)
Working mothers who just had their first child face major changes in aspects of their life. Workingmothers have two roles that must be fulfilled in their daily life, being a mother and a worker. Thedemands of these roles often create pressures that cause conflict within the mother herself.Conflicts that occur within herself are called intrapersonal conflicts. This study aims to overviewintrapersonal conflicts and perceived social support in mothers who return to work after havingtheir first child. The method used in this research is a qualitative method with semi-structuredinterview methods involving two participants who work professionally and have their first childaged 0-18 months. The results of this study indicate that there is an intrapersonal conflict in theroles of mother and worker. The type of conflict that arose in the two participants was the type ofmultiple/double approach-avoidance conflict in which the two alternative choices, working andcaring for children, both had negative and positive values for the participants. Both participantsstated that the existence of social support from people around them, can help participants dealwith intrapersonal conflicts when they have to work leaving their children.